Antimicrobial activity enhancement of MgO nanoparticles through Zn doping against multidrug-resistant bacteria - Benjamín Hernández-Figueroa; Guillermo Herrera-Pérez; Jesus S. Uribe-Chavira; Antonia Luna-Velasco; Alva Castillo-González; Blanca Sánchez-Ramírez; Claudia A. Ramírez-Valdespino; María R. Peralta-Pérez; Dayana E. Salas-Leiva; Edward A. Espinoza-Sánchez; Joan S. Salas-Leiva (Applied Surface Science Advances, 2025)
The structural, morphological, and antibacterial effects resulted from incorporating zinc into magnesium oxide (MgO) host lattice. Two samples were synthesized via the precipitation method with 10 and 16% zinc concentrations, and their properties were compared with those of a commercial (MgOc) sample. Structural analyses confirmed a cubic structure with space group Fm-3 m, which underwent distortions as Zn concentration increased. Microstructural studies via X-ray diffraction and transmission electron microscopy revealed nanoparticle (NPs) formation with a polyhedral morphology resulting from surface hydroxylation of cubic-shaped particles. Zinc incorporation and the presence of defects centers such as oxygen vacancies creates electronic states inside the bandgap reducing the bandgap energy value from 5.7 eV to 4.7 eV. Furthermore, an increase in Urbach energy was observed, suggesting greater energetic disorder due to the introduction of localized electronic levels within the bandgap. Zinc incorporation also increasing the average particle size. Antibacterial activity was evaluated based on IC50. For Staphylococcus aureus ATCC, IC50 values were 0.8 mg/mL and 0.49 mg/mL for commercial MgO NPs (MgOc) and MgO-Zn 10, respectively. In the case of S. aureus, multidrug-resistant (MDR) needed 2.81 mg/mL MgOc NPs, whereas IC50 was reduced to 0.69 mg/mL for MgO-Zn 10. For Pseudomonas aeruginosa ATCC, IC50 of MgOc NPs was 0.77 mg/mL, whereas a decrease of 0.34 mg/mL was observed for MgO-Zn 10. Concerning P. aeruginosa MDR, IC50 of MgOc NPs was 0.710 mg/mL, whereas a value lower than 0.5 mg/mL was recorded for MgO-Zn 10. These results suggest that using MgO‒Zn nanoparticles represents a promising strategy for combating multidrug-resistant bacteria.